Physical and Mechanical Characterization of Bamboo Fiber/Groundnut Shell/Copper Particle/MWCNT-Filled Epoxy Hybrid Polymer Nanocomposites. (5th September 2022) - Ramu, S.; Senthilkumar, N.; Rajendran, Saravanan; Deepanraj, B.; Abdeta, Dereje Bayisa
Abstract : Current research finds the suitability of natural fiber-reinforced polymer composites for industrial, automotive, marine, aerospace, and military vehicle applications, among others; they process being lightweight, high strength, ecofriendly, recyclable, and biodegradable. Bamboo fiber (Bambusoideae) mat, groundnut shell (Cocos nucifera) powder, copper particle, and multiwalled carbon nanotubes (MWCNT) fillers with epoxy resin are the primary materials. The key responsibility of MWCNT as a nanofiller is to improve the performance of materials by more than 80% and to attract the desirable properties such as high specific energy absorption of CNTs. An extensive investigation was carried out to determine the weight ratio between the total density and the water absorption rate of the composite. The maximal tensile and flexural strengths derived from EBGCM2 (E: epoxy; B: bamboo; G: groundnut shell; C: copper particle; M: MWCNT) were 50.66 MPa and 59.03 MPa, respectively. Addition of MWCNTs to specimens EBGCM2 and EBGCM3 and bonding the filler matrix by homogeneous mixing, but few nanoparticles are seen agglomerated. Flexural abilities of groundnut fiber/filler loading to strengthen the hybrid nanocomposites and the impact strength both quite improved than EB1 specimen. The neat epoxy and bamboo fiber composite (EB1) achieved 87.5 Shore-D hardness. SEM revealed (EBGCM3) improved interfacial adhesion between fiber and epoxy resin, but few nanoparticles are agglomerated, small molecules linked between the fibrous matrix, and the binding elements trapped in neighboring atoms, forming structural chains by the polymerization process.